Economisch belang en persoonlijk voorkeur: De rol van het vertalersechtpaar Székely-Lulofs in het cultureel transfer - Pusztai, Gábor (Acta Neerlandica, 2023)
The Dutch writer Madelon Székely-Lulofs and her husband László Székely played a veryimportant role in the cultural transfer between the Netherlands and Hungary in the thirtiesof the 20th century. They have translated several works of Dutch and Hungarian writersand wrote novels about the Dutch-East Indies. They chose writers who were successfuland well-known for their translations. Commercial success and personal interests alsoplayed a role in their choice of works to translate. As a results the works of Lajos Kassák,Sándor Márai, Ferenc Molnár, Lajos Zilahy, Jolán Földes, Mihály Földi, Zsolt Harsányi,Ferenc Körmendi and Gábor Vaszary were translated in Dutch. Books of Piet Bakker, Jande Hartog, Ary den Hertog, Klaas Nore and Anton Coolen were translated in Hungarian.